Amelioration of acidic soil using fly Ash for Mine Revegetation in Post-Mining Land - Akihiro Hamanaka; Takashi Sasaoka; Hideki Shimada; Shinji Matsumoto (International Journal of Coal Science & Technology, 2022)
Abstract This paper described the use of fly ash for soil amelioration of acidic soils to promote plant growth. In mining sites, acid sulfate soils/rocks, which contain sulfide minerals (e.g. pyrite FeS2), have appeared as a result of overburden excavation. The excessively acidic condition inhibits plant growth due to the dissolution of harmful elements, such as Al, Fe, and Mn. Fly ash, an alkaline byproduct of coal combustion generated in thermal power plants is expected to be adopted to ameliorate acidic soils. However, the mixing ratio of fly ash must be considered because excessive addition of fly ash can have a negative impact on plant growth due to its physical/chemical properties. The pot trials using Acacia mangium demonstrate the evolution of plant growth with a 5%–10% addition of fly ash into acidic soil. When the acidic soil has a high potential for metal dissolution, the metal ions leached from the acidic soil are large, making it difficult to improve plant growth due to osmotic and ionic stress. This work suggests that the effects of fly ash on metal ions leached from the soil have to be considered for the amelioration of acidic soil.